Climate-as-condition, the origins of climate change and the centrality of the social sciences. Issue 1 (March 2019) - Paterson, Matthew
This commentary seeks to extend and interrogate the notion of 'climate-as-condition' deployed in Bulkeley's paper. It does so by proposing that we complement the focus on how climate change is currently being made and remade, rather than appearing as a problem to which we respond, with an interrogation of the historical production of climate change by particular social forces and processes. In doing this, it seeks another way to insist on the centrality of the social sciences in understanding climate change. But it also suggests that the sorts of vignettes that Bulkeley develops may be understood differently if they are situated historically.